Attitudes of Dar Al Uloom University students towards practicing sports activity Through some demographic Variables: Evaluation study - Mohammed, Redhwan Ali (Journal of Educational and Psychological Sciences, 2022)
The study aimed to identify the attitudes of Dar Al Uloom University students towards practicing sports activities, the differences in these attitudes are investigated according to the variables (gender, college, educational level, body mass index). The study sample consisted of (234), including (131) male students and (103) female students who were chosen intentionally. The researcher used the descriptive analytical method as well as the questionnaire as a means of data collection, which included four areas (psychological, educational, health and fitness, and social domain). The study concluded that the students of Dar Al Uloom University have positive attitudes towards practicing sports activity in all fields of study arranged as follows (The field of health and fitness, the psychological field, the social field, and the educational field). The results also indicated that there were no differences in the attitudes of Dar Al Uloom University students towards practicing sports activity according to the variables (gender, college, and academic level), while there were statistically significant differences in these trends according to the BMI (body mass index) variable between those who have healthy weight verse overweight on one hand, and those who are overweight (obese) on the other hand, and in favour of those who are overweight (healthy weight and overweight). The study recommended the necessity of increasing the attention of the Sports Activity Unit to student affairs in the university by educating Dar Al Uloom University students about the importance of practicing physical and sports activity from the health, psychological, social, and educational aspects through periodic bulletins and educational lectures. Also activating the internal competitive sports competitions between the various faculties of the university to enhance social relations among students, as well as participating in external activities with other universities.